A study of venous thrombosis incidence in patients with acute hyperthyroidism. Issue 4 (1st April 2013) - Kim, D. D. W.; Chunilal, S.; Young, S.; Cutfield, R.
Abstract Background Hyperthyroidism is not a widely acknowledged risk factor for venous thrombosis (VT), such as deep vein thrombosis, pulmonary embolism and cerebral VT. Several case reports and case‐control studies support an association between VT and hyperthyroidism. Prothrombotic changes in the coagulation pathway in thyrotoxic subjects include reversible elevation of factor VIII and von Willebrand factor, and give biological plausibility to the association and possibly causation for VT. Aim We sought to determine the incidence of symptomatic VT in acute hyperthyroidism. Methods A retrospective review of consecutive outpatients presenting to the endocrinology clinic at our district hospitals from January 2006 to December 2008 with acute hyperthyroidism was carried out. All occurrences of objectively proven symptomatic VT (deep vein thrombosis, pulmonary embolism and cerebral vein thrombosis) in the 6 months following the diagnosis of hyperthyroidism were sought. Results Four hundred and twenty‐eight patients were identified, of whom most were female (80%) and relatively young (mean age 47 years). Three patients (0.70%: 95% confidence interval 0.14–2.0%) were identified with a confirmed VT within 6 months of the diagnosis of hyperthyroidism. Conclusions Although the literature suggests moderate association between VT and acute hyperthyroidism, our data show that the absolute risk is low. Furthermore, our data suggest that hyperthyroidism is usually an additional risk factor but rarely the sole risk factor for VT.